Trichodinids (Ciliophora: Peritrichida) of Mugil platanus (Mugiliformes: Mugilidae) and Micropogonias furnieri (Perciformes: Sciaenidae) from Samborombón Bay, Argentina, with the description of a new species - Marcotegui, Paula Soledad (2009)
During surveys of parasites of the whitemouth croaker Micropogonias furnieri (Desmarest) and the mullet Mugil platanus Gunther from Samborombon Bay, Argentina, Trichodina puytoraci, T. lepsii, T. jadranica, T. murmanica, Diparitella simplex and Trichodina scalensis sp. n. were morphologically studied. Taxonomic and morphometric data for these trichodinids based on dry silver nitrate-impregnated specimens are presented. This study is the first formal report of these trichodinids from the southwest Atlantic Ocean, and the description of a new species from M. platanus.